Molecule characterization of chemosensory and metabolism-related genes in the proboscis of Athetis lepigone - Tian, Cai-Hong; Liu, Xiao-Guang; Xu, Cun-Yi; Huang, Jian-Rong; Fu, Jun-Feng; Wang, Gen-Song; Zhang, Jun-Yi; Li, Guo-Ping; Yin, Xin-Ming; Feng, Hong-Qiang (Frontiers in Physiology, 2023)
Introduction: The moth species Athetis lepigone (Möschler) (Lepidoptera: Noctuidae), which has recently been identified as a pest of summer maize (Zea mays L.) in China, has demonstrated a rapid proliferation with in the Huang-Huai-Hai Plain region since its initial discovery in Hebei Province in 2005. It has become a prevalent pest of corn crops, and its ability to adapt quickly to its surroundings is currently being investigated. One of the key characteristics of its siphoning mouthparts is not only the feeding apparatus itself but also the chemosensory organs that enable the detection of chemical signals from the surrounding environment. However, there is a lack of comprehensive research on the genes responsible for chemosensory and metabolic mechanisms in the proboscises of male and female A. lepigone adults. Methods: In this study, we utilized transcriptome analysis to identify a total of fifty chemosensory genes from six distinct families, including 19 odorant-binding proteins (OBPs), 22 chemosensory proteins (CSPs), one co-receptor (Orco), six odorant receptors (ORs), four ionotropic receptors (IRs), and two sensory neuron membrane proteins (SNMPs) in the proboscis. Notably, seven OBPs, two CSPs, and one OR were discovered for the first time. Additionally, fourteen genes related to metabolism, including cytochrome P450 (CYPs) and carboxylesterases (CXEs), were also identified. Furthermore, a qualitative analysis was conducted on the relative transcript levels of eight related genes. The expression of 21 annotated chemosensory and metabolic genes was compared between A. lepigone adults and larvae using qRT-PCR, revealing tissue specificity. The majority of genes exhibited predominant expression in the antennae and proboscis during the adult stage, while showing slight expression in the combination of sixth-instar larval head oral appendages (maxilla, labium, and antenna) and pheromone gland-ovipositors of female adults. Results/discussion: Our study points to a new pest control strategies that these newly discovered genes have the potential to serve as targets for enhancing future pest control, including mating disruption and the use of food attractants. And it would be advantageous to ascertain the distribution of chemosensory gene expression and gain insights into the functionalities of these genes, thereby establishing a novel theoretical framework for the advancement of eco-friendly pesticides and efficient pest management strategies in the future.